Peningkatan Keterampilan Berpikir Kritis Siswa Melalui Model Pembelajaran Inkuiri Berbasis Laboratorium Pada Materi Pemantulan Cahaya - Rahmati, Rahmati; Sari, Novi Trina (Intelektualita: Journal of Education Sciences and Teacher Training, 2024)
This study aims to investigate the use of a laboratory-based inquiry learning model on improving students' critical thinking skills in the topic of light reflection. The research method used is a quasi-experiment with a control group pre-test and post-test design. Conclusions are drawn based on the processing and analysis of data using OriginLab. The data analysis results show the average critical thinking skill scores for the control and experimental groups are 27,90% (low) and 42,02% (moderate), respectively. This finding is further supported by the results of a t-test on the mean difference of critical thinking skill improvement (α=0,05), where the calculated tvalue (6,10) is greater than the ttable value (2,39). These results indicate that the laboratory-based inquiry learning model can significantly improve students' critical thinking skills compared to the conventional learning model on the topic of light reflection.